Total Thrombus-Formation Analysis System (T-TAS): Clinical Application of Quantitative Analysis of Thrombus Formation in Cardiovascular Disease - Kaikita, Koichi; Hosokawa, Kazuya; Dahlen, Jeffrey R.; Tsujita, Kenichi (Thrombosis and Haemostasis, 2019)
Various antithrombotic agents are clinically used to inhibit the cascade of arterial or venous thrombosis in cardiovascular diseases. Dual antiplatelet therapy with aspirin and P2Y12 inhibitors is prescribed in patients with coronary artery disease (CAD) undergoing percutaneous coronary intervention (PCI). Direct oral anticoagulants (DOACs) are widely used for the prevention or treatment of thromboembolism in patients with atrial fibrillation (AF) and venous thromboembolism. However, there has been no definitive tool to simultaneously monitor the antithrombotic effects of these drugs. The Total Thrombus-Formation Analysis System (T-TAS), a microchip-based flow chamber system that mimics in vivo conditions for evaluating whole blood thrombogenicity, was developed for the quantitative analysis of thrombus formation in whole blood specimens. The utility of T-TAS has been evaluated in CAD patients treated with antiplatelet therapies. The T-TAS PL chip area under the flow pressure curve (AUC) accurately assesses primary hemostasis and is sensitive to the therapeutic effects of various antiplatelet therapies. In addition, low AUC results are a significant predictor of periprocedural bleeding events in CAD patients undergoing PCI. The T-TAS AR chip AUC result is useful for assessing the efficacy of DOACs and warfarin in AF patients undergoing catheter ablation, and it is also a potential independent predictor of periprocedural bleeding events and avoidance of thrombosis in patients having undergone total knee arthroplasty. In conclusion, T-TAS is a useful index for evaluating the total antithrombotic effects of combination antithrombotic agents in patients with various cardiovascular diseases.
Keywords: T-TAS; antiplatelet therapy; direct oral anticoagulants; antithrombotic therapy; diagnostic test